EFFECT OF COVID-19 INFECTION ON CARDIOVASCULAR DISEASE - Abdushukurova Komila Rustamovna; Abdullaeva Guzal Maksudovna (Scholar Express Journals, 2024)
The coronavirus pandemic has had a drastic negative impact on global health indicators. To date, about 62 million cases of coronavirus infection have been identified around the world. According to WHO data, complications of the coronavirus disease with cardiovascular system diseases vary from 2.9% to 35.2% in different regions of the world. According to statistics, when complicated with cardiovascular diseases, 23.7% of patients with COVID-19 become seriously ill, and 10.7% of patients die. Patients suffering from coronavirus disease have a high risk of developing myocardial infarction on the 2-7th day of the disease, and it has been found that many patients do not have clinical symptoms characteristic of infarction
Keywords: coronavirus; myocardial infarction; angiotensin-converting enzyme inhibitor